The reality of applying internal marketing practices from the point of view of administrative employees In the branch of Mobilis Foundation in Laghouat - Metabis, Amel (Dirassat Journal Economic Issue, 2016)
The study aims to identify the reality of the application of internal marketing practices from the point of view of administrative staff in the branch institution mobilis in Laghouat. In order to achieve the objective of the study the researcher used descriptive –analytical approach on a sample consist of all employees under study. In addition, use questionnaire designed to measure assessments dimensions of internal marketing (the empowerment, the training, and the motivation). The statistical package for social science (SPSS) program was used to analyze and examine the hypotheses. The major finding of the study There is the application of internal marketing a medium degree.